2012
DOI: 10.1002/chin.201249019
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis, Structure and Magnetic Properties of La3Co2SbO9: A Double Perovskite with Competing Antiferromagnetic and Ferromagnetic Interactions.

Abstract: Reddish‐black polycrystalline powder of the title compound is prepared by solid state reaction of a stoichiometric mixture of La2O3, Co3O4, and Sb2O3 (950 °C for 12 h and 1400 °C for 12 h).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The AFM Co 2+ OCo 2+ and FM Co 2+ OM 5+ O Co 2+ super exchange interactions have been proposed in isostructural La 3 Co 2 SbO 9 . 27,28 Analogous to this scenario, an interplay between AFM Ni 2+ ONi 2+ and FM Ni 2+ O Nb 5+ ONi 2+ super exchange interactions is exceedingly probable in La 3 Ni 2 NbO 9 , which needs to be confirmed from the neutron diffraction studies. Therefore, coexistence of competing of FM and AFM interactions can be the origin of the magnetic frustration in this system.…”
Section: ■ Experimental Sectionmentioning
confidence: 97%
See 1 more Smart Citation
“…The AFM Co 2+ OCo 2+ and FM Co 2+ OM 5+ O Co 2+ super exchange interactions have been proposed in isostructural La 3 Co 2 SbO 9 . 27,28 Analogous to this scenario, an interplay between AFM Ni 2+ ONi 2+ and FM Ni 2+ O Nb 5+ ONi 2+ super exchange interactions is exceedingly probable in La 3 Ni 2 NbO 9 , which needs to be confirmed from the neutron diffraction studies. Therefore, coexistence of competing of FM and AFM interactions can be the origin of the magnetic frustration in this system.…”
Section: ■ Experimental Sectionmentioning
confidence: 97%
“…Low temperature neutron diffraction study of La 3 Co 2 SbO 9 confirmed that FM ordering temperature at 55 K was strongly dominated by the Co 2+ OSb 5+ OCo 2+ super exchange interaction. 28 It was further suggested that nature of FM order did not resemble typical long-range magnetic order, proposing a significant magnetic frustration. A relaxor FM behavior has been proposed for La 3 Ni 2 SbO 9 below 105 K. 30 At 5 K, any magnetic diffraction peak could not be detected from the neutron diffraction studies, further suggesting the relaxor behavior.…”
Section: ■ Introductionmentioning
confidence: 99%
“…14) which coincides well with the previously reported literature. [16][17][18]20 Thanks to the large neutron scattering intensity for oxygen atoms, accurate bond parameters correlated with oxygen are capable of being determined by neutron diffraction techniques. The cell parameters as well as the selected bond parameters are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…La 3 Co 2 SbO 9 shows the same cation ordering pattern as La 3 Ni 2 SbO 9 , but the sharp increase in magnetization observed in the latter at 108 K is not observed in the former. 6 Franco et al postulated that frustration prevents the development of long-range ferromagnetism, and their neutron diffraction data, collected at 2 K, contained a magnetic Bragg peak which they took to be indicative of an unidentified antiferromagnetically ordered structure. They have also studied 7 the system La 3 Ni 2−y Co y SbO 9 wherein they found a similarly ordered distribution of cations but no evidence for long-range magnetic ordering.…”
Section: ■ Introductionmentioning
confidence: 99%
“…6 All the Sr/La−O distances contract on cooling from 300 to 5 K, but the changes are not significant in the light…”
mentioning
confidence: 98%